Sociodemographic characteristics of male drivers participating in driver behavior development training and evaluation of the effect of training on self-control of individuals - Yılbaş, Barış (Journal of Dependence, 2021)
Objective: The aim of this study was to describe the sociodemographic data of drivers who were subjected to compulsory training and to evaluate the effect of individual interviews made by a psychiatrist on the self-control skills of the drivers.Method: 106 individuals were included in the study. In addition to the training, the drivers were interviewed twice by psychiatrist. To evaluate the effect on self-control skills, the self-control scale was applied to the volunteers in the 1st and 6th weeks.Results: All of the participants were male and twenty of the participants (18.9%) had substance use in some period of their lives, 27 (25.5%) had been in prison at least once. 78 of the participants (73.6%) answered yes to at least two questions in CAGE and their test average was 1.81 ± 0.83. Participants mean scores of 45.38 ± 14.83 from the self-control scale in the 1st week and 41.45 ± 14.57 from the 6th week were obtained.Conclusion: Compulsory education is insufficient in developing self-control skills of drivers. In addition, the high rate of substance use and crime in the participants indicates that the drivers participating in this training should be followed up in the psychiatric outpatient clinic at regular intervals.
Keywords: Traffic; alcohol; self-control